2018
DOI: 10.1523/jneurosci.1160-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Metabotropic Signaling Pathways Inhibit SK Channels to Promote Synaptic Plasticity in the Hippocampus

Abstract: Hebbian synaptic plasticity at hippocampal Schaffer collateral synapses is tightly regulated by postsynaptic small conductance (SK) channels that restrict NMDA receptor activity. SK channels are themselves modulated by G-protein-coupled signaling pathways, but it is not clear under what conditions these are activated to enable synaptic plasticity. Here, we show that muscarinic M1 receptor (M1R) and type 1 metabotropic glutamate receptor (mGluR1) signaling pathways, which are known to inhibit SK channels and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…A potential explanation lies in the compensation for deletion of M 3 with expression of M 1 receptors (Figure S4) that couple to similar Gq-mediated signalling pathways and it is interesting that knockin mutations of phosphorylation-deficient M 3 receptors with potentially less compensation show greater effects on learning and memory (Poulin et al, 2010). The compensation for M 3 deletion by M 1 receptors is somewhat surprising since M 1 receptors are generally expressed widely in somatic and dendritic cellular domains in pyramidal cells and interneurons where they regulate intrinsic excitability leading to effects on synaptic plasticity and network oscillations (Atherton et al, 2016; Betterton et al, 2017; Buchanan et al, 2010; Dennis et al, 2016; Fisahn et al, 2002; Levey et al, 1995; Mitsushima et al, 2013; Shinoe et al, 2005; Tigaret et al, 2018) but are not generally found in presynaptic terminals (Yamasaki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation lies in the compensation for deletion of M 3 with expression of M 1 receptors (Figure S4) that couple to similar Gq-mediated signalling pathways and it is interesting that knockin mutations of phosphorylation-deficient M 3 receptors with potentially less compensation show greater effects on learning and memory (Poulin et al, 2010). The compensation for M 3 deletion by M 1 receptors is somewhat surprising since M 1 receptors are generally expressed widely in somatic and dendritic cellular domains in pyramidal cells and interneurons where they regulate intrinsic excitability leading to effects on synaptic plasticity and network oscillations (Atherton et al, 2016; Betterton et al, 2017; Buchanan et al, 2010; Dennis et al, 2016; Fisahn et al, 2002; Levey et al, 1995; Mitsushima et al, 2013; Shinoe et al, 2005; Tigaret et al, 2018) but are not generally found in presynaptic terminals (Yamasaki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…S4) that couple to similar Gqmediated signalling pathways and it is interesting that knockin mutations of phosphorylation-deficient M 3 receptors with potentially less compensation show greater effects on learning and memory 67 . The compensation for M 3 deletion by M 1 receptors is somewhat surprising since M 1 receptors are generally expressed widely in somatic and dendritic cellular domains in pyramidal cells and interneurons where they regulate intrinsic excitability leading to effects on synaptic plasticity and network oscillations 12,[14][15][16]51,[68][69][70][71] but are not generally found in presynaptic terminals 72 .…”
Section: Discussionmentioning
confidence: 99%
“…Complex pre- and post-synaptic interactions between mGluRs and NMDARs, which reciprocally facilitate receptor function, have been described previously (e.g. Fitzjohn et al, 1996 ; Palmer et al, 1997 ; Krieger et al, 2000 ; Luccini et al, 2007 ; Perroy et al, 2008 ; Tigaret et al, 2018 ; for review see Reiner and Levitz, 2018 ). The molecular mechanisms through which these systems participate in the induction of LTD in juvenile hippocampus remain to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 66%